2005
DOI: 10.1176/appi.ajp.162.4.691
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Differences Between Late-Onset and Recurrent Geriatric Major Depression

Abstract: In contrast to recurrent geriatric major depressive disorder, late-onset major depressive disorder is characterized by specific deficits in tasks of attention and executive function, consistent with increased anhedonia and cardiovascular comorbidity. These findings, if confirmed, suggest that recurrent and late-onset geriatric major depressive disorder may represent distinct phenomenological entities. Such phenomenological differences as a function of lifetime history of major depression can guide research in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
147
2
9

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(165 citation statements)
references
References 41 publications
7
147
2
9
Order By: Relevance
“…These results provide further support for the conclusion that LLD patients as a whole are characterized by impairments of episodic memory, speed of information processing, executive functioning, and visuospatial ability [2][3][4][5][6][7][8]26], and that of these domains, information processing speed and executive functioning are particularly vulnerable. By circumventing the confounding effects of practice (i.e., performance change resulting from repeated testing) and time (often seen in progressive neurodegenerative diseases) in the current analyses, the robustness of this pattern of findings is enhanced.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…These results provide further support for the conclusion that LLD patients as a whole are characterized by impairments of episodic memory, speed of information processing, executive functioning, and visuospatial ability [2][3][4][5][6][7][8]26], and that of these domains, information processing speed and executive functioning are particularly vulnerable. By circumventing the confounding effects of practice (i.e., performance change resulting from repeated testing) and time (often seen in progressive neurodegenerative diseases) in the current analyses, the robustness of this pattern of findings is enhanced.…”
Section: Discussionsupporting
confidence: 69%
“…LLD has negative effects on quality of life, global functioning, physical health, as well as cognition, and up to half of individuals with LLD are estimated to have cognitive impairment greater than that of age-and education-equated comparison subjects [2,3]. Such cognitive deficits have been associated with higher depression relapse rates, poorer response to antidepressant treatment, and greater overall disability, and include impairments of episodic memory, speed of information processing, executive functioning, and visuospatial ability [2][3][4][5][6][7][8]. Of these domains, information processing speed and executive functioning are considered to be particularly vulnerable, and several studies have reported that cognitive impairment associated with LLD is predominantly mediated by slowed speed of information processing and/or working memory deficits [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…It is of note that depression that commences in late-life, as compared to that evident earlier, has been found to be associated with greater impairments in executive functioning (Alexopoulos, 2003;Rapp et al, 2005), and this has been attributed to the fact that executive control mechanisms are required to inhibit ruminative thinking once initiated (von Hippel et al, in press). The present results therefore support the possibility that there may be a qualitative distinction between the mild inhibitory failures characteristic of normal ageing relative to the more gross deficits characteristic of dementia with respect to their relationship with rumination (and consequently, depression).…”
Section: Depressionmentioning
confidence: 99%
“…This theory has been supported by MRI evidence in patients with geriatric depression of a higher incidence of white matter hyperintensities, representing deep white matter lesions of vascular origin (Camus et al, 2004). Further support for the vascular depression subtype comes from a study by Rapp et al which compared late-onset geriatric major depression to recurrent geriatric depression and found significantly more cardiovascular comorbidity (greater number of comorbid cardiovascular and cerebrovascular diagnoses) in the patients experiencing depression for the first time in their older age (Rapp et al, 2005). These findings suggest a relationship between depression that presents for the first time late in life and the degree of cardiovascular disease.…”
mentioning
confidence: 95%